Reformisati sebe i drugog / Reforming Self and Other - Tayob, Abdulkader (Context: Journal of Interdisciplinary Studies, 2022)
The Other occupies a dominant place in modern Islamic educational reform. Khayr al-Din al-Tunisi in the nineteenth-century urged Muslim educators to look at European developments, and questioned if the current approach followed in Muslim societies was beneficial. Muhammad ‘Abduh, in the twentieth century, identified one of the chief causes of decline in the influences exerted by ‘the beliefs and opinions introduced into Islam by different groups like the Sufis and others’. Deobandi madrasa in the Indian subcontinent pictured themselves as the forts of Islam (islam ke qile) protecting Muslims from the corrupting influence of Westernisation. In the last quarter of the twentieth century, Isma‘i‘ al-Faruqi framed the theory and plan of Islamisation in relation to Western social sciences, aiming to replace them with authentic, indigenous ones. It is clear that modern educational reformers have thought about reform in relation to a significant other. The West has often occupied a dominant place, but it is not the only partner through which reforms are conceptualised, planned and executed.